1984
DOI: 10.3168/jds.s0022-0302(84)81442-3
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of a Latex Teat Sealer

Abstract: In the first of two experiments, efficacy of a latex teat sealer product was tested under field conditions on 32 cows that had one side of the udder dipped with the test product and the other left as the control. Number of new coliform, staphylococcal, or streptococcal infections in treated quarters was not reduced from controls. In a second experiment, effectiveness of this product as a protective sealer was investigated on six cows dip challenged with a broth containing 1 million Escherichia coli/ml. On seal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
1
1

Year Published

2000
2000
2009
2009

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 16 publications
0
6
1
1
Order By: Relevance
“…However, the germicidal activity of the film might have been decreased and thereby been insufficient to prevent infection. It has been reported that the use of a barrier teat dip without germicidal activity did not prevent IMI in non-lactating udders (McArthur et al, 1984). It is also possible that teat dipping does not work in non-lactating animals against cow-dependent bacteria such as S. aureus, but only against environmental bacteria which were a minor problem in this herd.…”
Section: Discussionmentioning
confidence: 85%
“…However, the germicidal activity of the film might have been decreased and thereby been insufficient to prevent infection. It has been reported that the use of a barrier teat dip without germicidal activity did not prevent IMI in non-lactating udders (McArthur et al, 1984). It is also possible that teat dipping does not work in non-lactating animals against cow-dependent bacteria such as S. aureus, but only against environmental bacteria which were a minor problem in this herd.…”
Section: Discussionmentioning
confidence: 85%
“…An alternative, to the strictly preventive use of DCT, is to apply an internal, or external teat sealer 2 [3,4,27,35,42,44,45,46,73,88]. These sealers can be used in combination with DCT to obtain a preventive and a curative effect [26,45,46,47,68,84].…”
Section: Introductionmentioning
confidence: 99%
“…The overall mean average herd adherence was 4.40 ± 0.05 d (2,906 teats). This value exceeds what was reported in previous studies using lactating cow barrier teat dips during the dry period (McArthur et al, 1984;Matthews et al, 1988). The current teat sealant product used (DryFlex) was a revised version of the previous formulation (Stronghold).…”
Section: Discussionmentioning
confidence: 62%
“…Nevertheless, there is evidence to suggest that the ability of the product to reduce the level of infection at calving is related to the duration of adherence at drying off (Timms, 2001). Researchers have suggested that the lack of prolonged adherence could be the reason bene-ficial results were absent in their studies (McArthur et al, 1984;Matthews et al, 1988). In one study, none of the sealants lasted more than 24 h (Matthews et al, 1988).…”
Section: Introductionmentioning
confidence: 99%